Digital media use and sleep in late adolescence and young adulthood: A systematic review. (April 2023) - Brautsch, Louise AS.; Lund, Lisbeth; Andersen, Martin M.; Jennum, Poul J.; Folker, Anna P.; Andersen, Susan
Abstract: Despite much attention on digital media use and young peoples' sleep, the literature on digital media and its impact on sleep in older adolescents and young adults remains to be synthesized. We conducted a systematic review of studies including young people aged 16–25 years. We searched Medline, Web of Science, and CINAHL for observational studies, identifying 60 studies. These studies were assessed for methodological quality. Only studies rated as moderate or high-quality studies were included (n = 42). A narrative synthesis summarized the impact of digital media use on eight sleep outcomes: Bedtime; Sleep onset latency or problems falling asleep; Sleep duration; Early awakening; Sleep disturbance; Daytime tiredness and function; Sleep deficits; Sleep quality. In summary, digital media use was associated to shorter sleep duration and poorer sleep quality. These associations were found for general screen use and use of mobile phone, computer, internet, and social media, but not for television, game console, and tablet use. Most studies investigating bedtime or nighttime use found associations to poor sleep outcomes. Later bedtime and daytime tiredness were associated with mobile phone use at night. Additional research is warranted to draw solid conclusions about the causal direction and to understand the underlying mechanisms.